Human Cytosolic Sulphotransferase SULT1C3: genomic analysis and functional characterization of splice variant SULT1C3a and SULT1C3d. (29th June 2017) - Kurogi, Katsuhisa; Shimohira, Takehiko; Kouriki-Nagatomo, Haruna; Zhang, Guisheng; Miller, Ethan R; Sakakibara, Yoichi; Suiko, Masahito; Liu, Ming-Cheh
Abstract: The cytosolic sulphotransferase SULT1C3 remained the most poorly understood human SULT. The SULT1C3 gene has been shown to contain alternative exons 7 and 8, raising the question concerning their evolutionary origin and implying the generation of multiple SULT1C3 variants. Two SULT1C3 splice variants, SULT1C3a and SULT1C3d, were investigated to verify the impact of alternative C-terminal sequences on their sulphating activity. Sequence homology and gene location analyses were performed to verify the orthology of the SULT1C3 gene. The SULT1C3 gene appears to be present only in humans and other primates, but alternative exons 7b and 8b share high degrees of homology with corresponding regions of rodent SULT1C1 genes, implying their evolutionary origin being from a defunct human SULT1C1 gene. Purified recombinant SULT1C3a and SULT1C3d were analyzed for sulphating activities toward a variety of endogenous and xenobiotic compounds. While SULT1C3a displayed weaker activities and strict substrate specificity toward hydroxyl-chlorinated biphenyls, SULT1C3d exhibited broader substrate specificity toward bile acids and thyroid hormones as well as hydroxyl-chlorinated biphenyls. Molecular docking simulation suggested that Tyr249 and Met257 may play an important role in substrate recognition by SULT1C3d. Alternative splicing of exons 7 and 8 sequences resulted in differential catalytic properties of SULT1C3 variants.